Anaerobic membrane bioreactor fouling control with quorum quenching effect - Lek, Zhi Yu (2019)
Recently quorum quenching (QQ) is proven to be effective as an innovative solution for biofouling mitigation on membrane bioreactor system under aerobic condition. Numerous researches have been done to optimize the QQ effect on aerobic membrane bioreactor (AeMBR) system. In comparison, the anaerobic membrane bioreactor (AnMBR) offer numerous advantages compared to its aerobic counterparts. In spite of that, there is little research on the application of the QQ effect is feasible in an AnMBR. Therefore a study to investigate the application of QQ effect for membrane biofouling control in AnMBR could provide an improvement in wastewater treatment technology. In this study, we work on to select the most effective QQ bacterial strain, entrapped in polysulfone coated alginate beads and applied in a laboratory scale AnMBR system to study the effectiveness in biofouling control. The transmembrane pressure (TMP) increase, usually an indication of membrane fouling, was successfully prolonged by 10 times under constant flux condition with the application of QQ bacteria. The Acyl-homoserine lactones (AHLs) concentration in sludge and bio cake reflect a significantly lower concentration in the reactor containing QQ bacterial entrapped in beads compared to the control experiment. Furthermore, the reactor with QQ bacterial also reflects a much lower extracellular polymeric substance (EPS). Furthermore, results proved that the QQ effect does not have any influence on the biological treatment performance of the AnMBR system. It is also noted that with the application of QQ bacterial entrapped in beads increase the methane yield of the process. These results suggest that QQ bacterial entrapped in beads is effective and feasible in the application of an AnMBR system for biofouling control. The results provide the basis of further study to optimize biofouling control on AnMBR with the QQ effect.